2019
DOI: 10.3171/2017.12.jns17281
|View full text |Cite
|
Sign up to set email alerts
|

The economic consequences of neurosurgical disease in low- and middle-income countries

Abstract: OBJECTIVE The objective of this study was to estimate the economic consequences of neurosurgical disease in low- and middle-income countries (LMICs). METHODS The authors estimated gross domestic product (GDP) losses and the broader welfare losses attributable to 5 neurosurgical disease categories in LMICs using two distinct economic models. The value of lost output (VLO) model projects annual GDP losses due to neurosurgical disease during 2015-2030, and is based on the WHO's "Projecting the Economic Cost of Il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…[33] A number of studies have utilised similar methodology to estimate the economic value of lost welfare associated with various diseases. [24,[34][35][36] respectively. Although, the differing sample populations, years of analysis and incorporated assumptions preclude direct comparison between our results, it is reassuring that they do not appear grossly disproportionate to those reported in this study.…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…[33] A number of studies have utilised similar methodology to estimate the economic value of lost welfare associated with various diseases. [24,[34][35][36] respectively. Although, the differing sample populations, years of analysis and incorporated assumptions preclude direct comparison between our results, it is reassuring that they do not appear grossly disproportionate to those reported in this study.…”
Section: Accepted Articlementioning
confidence: 99%
“…Similarly, although there will likely be some debate regarding the estimates of disease burden mandating neurosurgical consultation and intervention, in the absence of more compelling information from a range of settings, we thought it reasonable to derive these proportions from a geographically and socio-economically representative sample of neurosurgeons, [21] which is consistent with previous similar studies. [24,[34][35][36] We also acknowledge that the application of a uniform proportion of surgical burden to all countries is likely to be simplistic. Indeed, given that focal epilepsy appears to be more prevalent in LICs and LMICs, it is possible that epilepsy surgery has a greater role in these settings than it does in more developed countries, although this proposal remains conjectural and any attempt to account for it in this analysis would be speculative.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…2 Last, Rudolfson et al showed that, just in the 90 LMICs, neurosurgical conditions, largely unmet at present, will result in $4.4 trillion in cumulative gross domestic product losses by 2030. 8 Taken collectively, there is a compelling moral, ethical, and economical argument for the neurosurgical community to work alongside the global surgery community and development partners to advocate for strengthening emergency and essential surgical care in the LMICs. Future research in global neurosurgery is urgently needed as neurosurgeons are increasingly being asked to provide technical and strategic guidance to policymakers in building capacity to meet the global neurosurgical workforce and case deficit.…”
mentioning
confidence: 99%
“…I n this issue of the Journal, I am pleased to highlight and promote the publication of 9 new articles on the topic of global neurosurgery. [4][5][6][7][8][9][10]12,13 Many of the articles in this issue are derived from the efforts of authors from the Global Neurosurgery Initiative and the Program in Global Surgery and Social Change at Harvard and their numerous collaborators. These articles follow on the heels of a recent issue in Neurosurgical Focus (Volume 45: Issue 4, October, 2018) that was entirely devoted to reducing inequities in global neurosurgery delivery.…”
mentioning
confidence: 99%